2021
DOI: 10.3390/nano11020256
|View full text |Cite
|
Sign up to set email alerts
|

Starch-Capped AgNPs’ as Potential Cytotoxic Agents against Prostate Cancer Cells

Abstract: One of the major therapeutic approaches of prostate cancer (PC) is androgen deprivation therapy (ADT), but patients develop resistance within 2–3 years, making the development of new therapeutic approaches of great importance. Silver nanoparticles (AgNPs) synthesized through green approaches have been studied as anticancer agents because of their physical-chemical properties. This study explored the cytotoxic capacity of starch-capped AgNPs, synthesized through green methods, in LNCaP and in PC-3 cells, a horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Most proliferating cancer cells tend to arrest in different cell cycle phases when they come across stress conditions, including glucose and glutamine deprivation, or encounter chemical drugs or products, extracts, and NPs from diverse biological sources with cytotoxic potential. 51,[70][71][72][73] Cell cycle arrest provides an opportunity to promote the repair of damaged DNA or trigger the elimination of damaged cells via apoptosis. Investigating cell cycle progression and apoptotic mode of cell death is thus required for the effective screening of prospective therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Most proliferating cancer cells tend to arrest in different cell cycle phases when they come across stress conditions, including glucose and glutamine deprivation, or encounter chemical drugs or products, extracts, and NPs from diverse biological sources with cytotoxic potential. 51,[70][71][72][73] Cell cycle arrest provides an opportunity to promote the repair of damaged DNA or trigger the elimination of damaged cells via apoptosis. Investigating cell cycle progression and apoptotic mode of cell death is thus required for the effective screening of prospective therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, silver nanoparticles have been studied owing to their specific physicochemical properties and their great potential in killing cancer cells [ 3 ]. Recently, it has been shown that starch-capped silver nanoparticles, synthesized through a green method, successfully induced damage in cytoplasmic membranes and mitochondria, leading to cell cycle arrest and consequent blockage of cell proliferation and death in prostate cancer cells, showing the potential of silver nanoparticles as anticancer agents [ 4 ]. Nanomedicine has been shown to overcome some of the limitations of current drugs used in cancer treatment, such as poor water solubility, lack of specificity to the tumor site, and systemic side effects [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue comprises eleven research articles and two reviews. Most of the studies use classical AgNPs with different sizes and coatings, but some of them uses more innovative variations of this products, such as silicon-based silver dendritic nanoforest [ 1 ] or starch-capped AgNPs [ 2 ].…”
mentioning
confidence: 99%
“…Another work synthesized starch-capped AgNPs and studied their possible use as cytotoxic agents against prostate cancer cells. The study concluded that starch-capped AgNPs successfully damage cancer cell lines; therefore, they are proposed as anticancer agents [ 2 ]. Alumina-supported AgNPs were also proposed as catalysts for betulin oxidation.…”
mentioning
confidence: 99%